2018
DOI: 10.1111/jzo.12614
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intraspecific differences in leaf beetle attachment on rigid and compliant substrates

Abstract: The influence of substrate stiffness on the attachment ability of insects has been largely neglected so far. In the present study, traction experiments with adult beetles Gastrophysa viridula and Leptinotarsa decemlineata were carried out to study the influence of smooth, non-structured surfaces, having different stiffness, on beetle attachment. Force measurements were performed with tethered walking adult insects, both males and females, intact and after removal of claws, on hydrophilic (normal) and hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Original brightness and contrast have been increased to improve image clarity. [6,7] attachment ability [65,66]. Moreover, studies on the soft-bodied caterpillars of the tobacco hornworm, Manduca sexta L. (Lepidoptera, Sphingidae), revealed that substrate stiffness can be an essential component of a mechanical system in terms of locomotion (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Original brightness and contrast have been increased to improve image clarity. [6,7] attachment ability [65,66]. Moreover, studies on the soft-bodied caterpillars of the tobacco hornworm, Manduca sexta L. (Lepidoptera, Sphingidae), revealed that substrate stiffness can be an essential component of a mechanical system in terms of locomotion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, their individual relevance in the context of leech attachment strongly depends on the surrounding medium, as well as on the shape and structure of the respective substrate involved. Furthermore, recent studies on ladybird beetles Coccinella septempunctata L. and leaf beetles Gastrophysa viridula DeGeer and Leptinotarsa decemlineata Say (Coleoptera, Coccinellidae and Chrysomelidae, respectively) revealed a positive correlation between the stiffness of a substrate and the respective attachment ability [65,66]. Moreover, studies on the soft-bodied caterpillars of the tobacco hornworm, Manduca sexta L. (Lepidoptera, Sphingidae), revealed that substrate stiffness can be an essential component of a mechanical system in terms of locomotion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous suggestions for a sexually selected functional morphology of attachment devices were derived from a male-limited presence or male-specific geometry of attachment structures, or the observation that beetle males adhered to females during mating and mate guarding (Aiken and Khan, 1992;Bergsten et al, 2001;Voigt et al, 2008Voigt et al, , 2012Voigt et al, , 2017bVoigt et al, , 2019Karlsson Green et al, 2013;Gloyna et al, 2014). Larger attachment forces may benefit males in withstanding dislodging attempts by defensive body flicking movements of females (Reinhardt et al, 2009) or competing males (Schanz, 1953;Pelletier and Smilowitz, 1987;Voigt et al, 2008Voigt et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…For example, attachment structures were limited to, or more elaborated in males, or were hypothesised or shown to facilitate uninterrupted copulation by clasping, such as in leaf beetles, ladybirds, diving beetles and mirid bugs (e.g. Plateau, 1872;Schanz, 1953;Stork, 1980aStork, ,b, 1981Pelletier and Smilowitz, 1987;Aiken and Khan, 1992;Gorb, 2001;Bergsten et al, 2001;Voigt et al, 2008Voigt et al, , 2017bVoigt et al, , 2019Bullock and Federle, 2009;Karlsson Green et al, 2013;Heepe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is common knowledge that in house geckos, the ability to walk on walls are thanks to attachment pads located on the digits of their legs, and it is not unreasonable to assume that insects have the same mechanism to traverse steep surfaces [1][2][3][4][5]. Stick insects [3,[6][7][8][9][10], certain variety of beetles [4,[11][12][13][14][15], cockroaches [16][17][18][19], and most famously flies [20,21] are just some examples of insects using adhesion to scale steep surfaces. However, adhesion is not the only means of attaching to surfaces securely.…”
Section: Discussionmentioning
confidence: 99%